Social Networking Sites, Personalization, and Trust in Government: Empirical Evidence for a Mediation Model - Christopher Starke (Social Media + Society, 2020)
Political communication via social media might well counter the eroding political trust. In particular, social networking sites (SNS) enable direct flows of communication between citizens and the political elite, thereby reducing social and political gaps. Based on the concept of personalization of politics , we argue that interactions with politicians on SNS affect trust in government through a two-step process: First, interactions on SNS make citizens evaluate politicians’ characters more favorably. Second, these evaluations serve as cues for the citizens to develop or withdraw trust in government. We test indirect effects using four character traits as mediators: leadership, benevolence, responsiveness, and likeability. A representative online survey ( n  = 1117; in Germany) reveals that interactions with politicians on SNS increase the perceived likeability of candidates, and thus also trust in government. However, they do not affect the evaluation of the other traits: leadership, benevolence, and responsiveness.